A scoping review of capital adequacy ratios across different banking systems: Effects on bank market value and stability - Benlaria, Ahmed; Mouna, Younes (The International tax journal, 2025)
This scoping review systematically maps and synthesizes research on the effects of bank capital adequacy ratios on market value and stability across diverse banking systems, a topic of persistent debate following global regulatory reforms like Basel III. Analyzing 50 empirical studies published from 2000-2024, the review identifies key themes, regional variations, and knowledge gaps. A strong consensus emerges from the literature confirming that higher capital adequacy consistently enhances bank stability by improving shock absorption capacity across different economic contexts. In contrast, the relationship with profitability and market value is highly heterogeneous, revealing complex trade-offs between regulatory costs and market confidence benefits that are moderated by regional, institutional, and macroeconomic factors. Significant variations documented between developed and emerging markets challenge the efficacy of a one-size-fits-all regulatory approach. The findings underscore the need for context-sensitive frameworks and identify critical research priorities, including long-term Basel III impact assessments and cross-regional comparative analyses to address current geographic imbalances in the evidence base.